Phosphorus-containing mesoporous carbon acid catalyst for methanol dehydration to dimethyl ether. - Valero-Romero, María José; Calvo-Muñoz, Elisa Maria; Ruiz-Rosas, Ramiro Rafael; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (ACS Publications, 2019)
Catalytic dehydration of methanol on an acid carbon catalyst prepared by chemical activation of olive stone with H3PO4 is reported. This preparation methodology produces carbons with a well-developed porous texture and highly thermally stable phosphorus surface complexes in form of C–O–PO3 and C–PO3. These P groups confer the carbon with a high oxidation resistance, surface acid and redox sites. In the absence of oxygen, the catalyst experimented a gradual deactivation due to coke deposition on the strong acid sites (P-OH) and reduction of the moderate-strength acid P-surface groups (from C–O–P to C–P type ones). The novelty of this research concerns the high catalytic stability in air atmosphere of this type of carbon with a steady state methanol conversion of 20% at 300ºC and selectivity towards dimethyl ether of 95%. The presence of oxygen in the reaction gas avoids coke deposition by continuously (re)oxidation of reduced P-surface groups, without gasification of the carbon catalyst.
Keywords: Catalizadores; Carbono; Fósforo; Metanol (Combustible); Activated carbon; Methanol dehydration; Dimethyl ether; Phosphorus; Surface acidity